The effects of ZnO coating on the photoluminescence properties of porous silicon for the advanced optoelectronic devices - Prabakaran, R. (2008)
In the present work we investigate, the role of zinc oxide (ZnO) thin films passivating layer deposited by rf magnetron sputtering at room temperature on low (18%) and high (80%) porosity porous silicon (PS). The micro-Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR) and atomic force microscopy (AFM) analysis have been carried out to understand the effect of ZnO films coating on PS. A systematic investigation from Raman spectroscopy suggests the formation of a good quality ZnO wurtzite structure on PS. The photoluminescence (PL) measurements on PS and ZnO coated PS shows a red, blue and UV emission bands at around ∼1.8, ∼2.78 and ∼3.2 eV. An enhancement of all PL emission bands have been achieved after ZnO films deposition on high porosity PS.